Concentration of micro-elements and pollutant elements in cauliflower (Brassica oleracea convar botrytis var botrytis) - BRAR, M S; ARORA, C L (The Indian Journal of Agricultural Sciences, 2013)
Samples of soils and the leaves and curds of cauliflower [Brassica oleracea 1. convar batrylis (L.) Alef. var botrytis L.]were collected from farmers’ fields irrigated with tube-well water and supplied with farmyard manure, tube-well water and city refuse, and sewage water. Contents of Zn, Cu, Fe, Mn, Pb and Ni were 21.4, 18.1,29.8,11.8; 5.1 and 1.3 mg/kg in the soils irrigated with sewage water compared with 3.6, 5.1,8.6,9.9, 1.5 and 0.08 mg/kg in soils irrigated with tube-well water and supplied with farmyard manure respectively. The concentration of these elements in the leaves was 39.5, 4.1, 149.0,33.7,0.97 and 1.1 mg/kg when grown on soils inigated with sewage water compared with 31.6,3.6, 101.0, 29.9,1.28 and 0.57 mg/kg on soils irrigated With tube-well water and supplied with farmyard manure. Their concentration in curds was 49.0, 2.9, 149.4, 22.6, 1.87 and 1.93 mg/kg when irrigated with sewage water compared with 39.3, 4.4, 114.4,19.8, 1.47 and 1.03,mg/kg on soils irrigated with tube-well water and supplied with farmyard manure. Nickel and lead accumulated in the soils irrigated with sewage water, but plants did not absorb these elements in proportion to their concentrations in the soils, Curds of cauliflower had the tendency to accumulate higher amounts of pollutant elements than the leaves: